Pengaruh Kompres Dingin Ice Bag Terhadap Nyeritenggorokan Post Intubasi Dengan General Anestesi di RS PKU Muhammadiyah Yogyakarta - Hasbi Ikhsanuddin; Niken Anggraini Sri Saputri; Vita Purnamasari (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Sectio caesarea is one of the surgical delivery methods performed when normal delivery is not possible. Although this procedure is considered safe, prospective patients often experience high stress due to fear of surgery, interventions such as religious music therapy that have spiritual value can calm emotions. This study aims to determine the effect of religious music therapy on stress levels in pre-section caesarean patients at RSUD dr. Tjitrowardojo Purworejo. This study used a quasi-experimental design with a non-randomized control group pretest-posttest design approach. The study sample was 30 patients who were divided into two groups, namely 15 people as the intervention group and 15 people as the control group. The research instruments were music therapy and stress level questionnaires. To analyze the data, the Wilcoxon Signed Rank Test and the Mann-Whitney Test were used.. The results showed a significant decrease in patient stress levels after listening to religious music. The average stress score before the intervention was higher than after the intervention, and the statistical test showed a p value <0.05, which means that religious music therapy has a significant effect on reducing stress. Religious music therapy can reduce stress levels in pre-cesarean section patients. This intervention can be used as part of anesthesia maintenance to improve patient comfort and mental readiness before surgery.